Inventarisasi Bryophyta Di Kawasan Hutan Pinus Kragilan Kabupaten Magelang Provinsi Jawa Tengah - Endarwati, Eli; , Efri Roziaty, S. Si., M. Si (2017)
Bryophyte is a group of low level plants found growing in tree, wood rotted, dead wood, soil and rocks with damp environmental conditions. In pine forest area Kragilan Magelang have stations composed of 1300-1400 meters above sea level, an area of ±7,7 Ha, precipitation and humidity is high so the Moss can grow. The purpose of this research is to know the inventory bryophyte in pine forest area Kragilan Magelang Regency of Central Java Province. The research on the study of ecology of bryophyte in the forest area of pine implemented Kragilan 22 Februari-01 Juli 2017. The sampling technique used method Purposive Random Sampling. Research results inventory bryophyte found12 familia includes 17 species that Anthoceros sp., Pogonatum cirrhatum, Thuidium delicatulum, Polytricum commune, Fissidens fontanus, Rhodobryum roseum, Bryum argenteum, Phyrrhobryum spiniforme, Isopterygium minutirameum, Thuidium tamariscinum, Aerobryopsis longissima, Lophocolea sp., Marchantia polymorpha, Marchantia geminata, Marchantia chenopoda, Riccia sp., Octoblepharum albidium.